Passive Diffusion vs Active pH-Dependent Encapsulation of Tyrosine Kinase Inhibitors Vandetanib and Lenvatinib into Folate-Targeted Ferritin Delivery System - Skubalova, Zuzana; Rex, Simona; Sukupova, Martina; Zahalka, Martin; Skladal, Petr; Pribyl, Jan; Michalkova, Hana; Weerasekera, Akila; Adam, Vojtech; Heger, Zbynek (International journal of nanomedicine, 2021)
INTRODUCTION: The present study reports on examination of the effects of encapsulating the tyrosine kinase inhibitors (TKIs) vandetanib and lenvatinib into a biomacromolecular ferritin-based delivery system. METHODS: The encapsulation of TKIs was performed via two strategies: i) using an active reversible pH-dependent reassembly of ferritin´s quaternary structure and ii) passive loading of hydrophobic TKIs through the hydrophobic channels at the junctions of ferritin subunits. After encapsulation, ferritins were surface-functionalized with folic acid promoting active-targeting capabilities. RESULTS: The physico-chemical and nanomechanical analyses revealed that despite the comparable encapsulation efficiencies of both protocols, the active loading affects stability and rigidity of ferritins, plausibly due to their imperfect reassembly. Biological experiments with hormone-responsive breast cancer cells (T47-D and MCF-7) confirmed the cytotoxicity of encapsulated and folate-targeted TKIs to folate-receptor positive cancer cells, but only limited cytotoxic effects to healthy breast epithelium. Importantly, the long-term cytotoxic experiments revealed that compared to the pH-dependent encapsulation, the passively-loaded TKIs exert markedly higher anticancer activity, most likely due to undesired influence of harsh acidic environment used for the pH-dependent encapsulation on the TKIs' structural and functional properties. CONCLUSION: Since the passive loading does not require a reassembly step for which acids are needed, the presented investigation serves as a solid basis for future studies focused on encapsulation of small hydrophobic molecules.
Keywords: buněčná smrt; nosiče léků; Biocompatible Materials; Drug Carriers; Cell Line; buněčné klony; Phenylurea Compounds; Cell Movement; Quinazolines; Quinolines; Protein Kinase Inhibitors; Folic Acid; koncentrace vodíkových iontů; povrchové vlastnosti; biokompatibilní materiály; lékové transportní systémy; vandetanib; Antineoplastic Agents; nanomedicine; kyselina listová; Horses; chinazoliny; Cell Death; Surface Properties; Animals; Piperidines; protinádorové látky; zvířata; Humans; difuze; Hydrogen-Ion Concentration; pohyb buněk; koně; Diffusion; drug delivery; lenvatinib; buněčné linie; inhibitory proteinkinas; Drug Delivery Systems; ferritiny; piperidiny; Clone Cells; chinoliny; lidé; Ferritins; fenylmočovinové sloučeniny